Impact of Age and Physical Activity on Postprandial Metabolic Responses (OR22-07-19). (13th June 2019) - Koemel, Nicholas; Sciarillo, Christina; Tomko, Patrick; Bode, Katherine; Jenkins, Nathaniel; Emerson, Sam
Abstract: Objectives: Large metabolic responses to high-fat meals (HFM) are known to create a deleterious physiological state. However, there is limited research describing the differential influences of age and physical activity level on meal metabolism, specifically in healthy older individuals. The goal of this project is to quantify the impact of age and physical activity on metabolic outcomes immediately following meal consumption in healthy men and women. Methods: We recruited 4 groups of individuals: younger active (YA; age 22.3 ± 1.5 y; n = 7), younger inactive (YI; age 22.6 ± 4.0 y; n = 7), older active (OA; age 70.5 ± 7.8 y; n = 6), and older inactive (OI; age 69.6 ± 7.6 y; n = 5). Following a 10-hour overnight fast, an intravenous catheter was inserted into a forearm vein from which a fasting blood draw was taken. Participants then consumed a HFM (12 kcal/kg; 63% fat, 34% carbohydrate). Serial blood draws were conducted hourly for 6 hours to measure postprandial triglyceride (TG) and glucose (GLU) responses. Prior to the HFM, participants refrained from exercise for 48 hours to remove the confounding effects of recent acute exercise. One-way or two-way ANOVA was used, as appropriate, to compare groups with regard to postprandial metabolic outcomes. Results: Groups were similar with regard to fasting GLU ( P = 0.77) and TG ( P = 0.06). There was a time effect for both GLU and TG in the postprandial period ( P < 0.0001). A group effect was present for TG ( P = 0.048), but not GLU ( P = 0.07). There were no significant group differences in TG in post hoc comparisons (YA vs. YI, P = 0.41; YA vs. OA, P > 0.99; YA vs. OI, P = 0.08; YI vs. OA, P = 0.42; YI vs. OI, P = 0.67; OA vs. OI, P = 0.08). Total area under the curve (AUC) for TG was significantly different across groups ( P = 0.0498; YA = 618.8 ± 103.1 mg/dL x 6 hr, YI = 836.4 ± 402.6, OA = 609.0 ± 234.6, OI = 993.4 ± 80.9), but incremental AUC was not different ( P = 0.18). Groups did not differ with regard to GLU total ( P = 0.07) or incremental AUC ( P = 0.26). Peak TG ( P = 0.38) and GLU ( P = 0.18) responses did not differ across groups. Conclusions: In this ongoing experiment, we are observing group differences in postprandial TG based on age and physical activity level. When complete, this study will highlight the independent effects of aging and physical activity on postprandial metabolic responses, which are integral components in CVD risk. Funding Sources: Oklahoma State University.